Bulgarian Entrepreneurship in the United Europe: Challenges and Opportunities - Todorov, Kiril (UNWE Yearbook, 2007)
The paper aims to identify the challenges (dangers) and the openings confronting Bulgarian companies, entrepreneurs and managers as a consequence of the country’s accession to the EU. For this object, I have analysed the positive and the negative impacts on business in the 10 new members of the EU, as well as the conditions of the Bulgarian small and medium-size businesses and the readiness of its entrepreneurs and the managers.Based on the findings of the analysis, the guidelines for possible solutions of the problems thus identified and the emerging business opportunities in the EU have been formulated. The recommendations for the solutions target all institutions and vested interests concerned – “policy makers"; employers’ and sectoral organizations; companies, businesses, entrepreneurs, managers, researchers, coaches and consultants.